FABRICATION AND CHARACTERIZATION OF UZM-5/POLYSULFONE MIXED MATRIX MEMBRANE FOR CO2 /CH4 GAS SEPARATION - TAN, GARY YIH LUEN (2023)
The environment receives a substantial amount of carbon dioxide from industrial gas emissions, particularly natural gas, which contributes to greenhouse gases and global warming. Gas separation technology is therefore crucial for removing CO2.